Akad Sewa Menyewa Lahan Sawah dengan Sistem Rendeman Persepektif Hukum Ekonomi Syariah (Studi Kasus di Dusun Potok Barat Desa Sukowono Jember) - Bachrul Ulum; Silvi Ivana Ramadhani (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
The form of cooperation in muamalah is the leasing activity that is common in society. This transaction is basically permitted in Islam if it fulfills the pillars and conditions because not everyone is able to meet their needs without the help of others. but whether the lease is legal or still violates sharia economic law. Because many people or communities do everything possible to get money without thinking it is legal or not. The purpose of the research is to find out the review of sharia economic law on the practice of leasing rice fields with a rendeman system in the western potok hamlet of Sukowono village, Sukowono sub-district, Jember district. The research method used is descriptive qualitative research using primary and secondary data sources and data collection methods with observation, interviews and documentation. While the data analysis used is descriptive analysis, to test the validity of the data and researchers use source triagulation. From the results of this study, the lease agreement with the rice field rendeman system in Sukowono village from the perspective of Islamic economic law is not justified because it violates the pillars of Ijarah, namely Muta'aqidain which can be called mu'jir and musta'jir, namely the person who has the benefit of the Ijarah. This means that there are two actors renting rice fields based on Islamic law, there is no second party (third tenant / musta'jir shani) in the pillars of ijarah.